1996
DOI: 10.1164/ajrccm.153.4.8616577
|View full text |Cite
|
Sign up to set email alerts
|

Balance between alveolar macrophage IL-6 and TGF-beta in lung-transplant recipients. Marseille and Montréal Lung Transplantation Group.

Abstract: Acute inflammation in the lung is characterized by a phase of tissue injury followed by a phase of tissue repair. When the latter is excessive, fibrosis occurs. Alveolar macrophages (AM) can produce cytokines involved in both phases of acute lung inflammation, notably interleukin-6 (IL-6), involved in injury and transforming growth factor-beta (TGF-beta), mediating repair. We hypothesized that AM were activated in both phases, and studied IL-6 and TGF-beta production by AM during complications of lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 0 publications
5
59
0
Order By: Relevance
“…22,28 Vast arrays of cytokine and chemokine networks (those implicated include tumor necrosis factor-␣, IL-2, IL-8, RAN-TES [regulated upon activation, normal T-cell expressed and secreted], platelet-derived growth factor, transforming growth factor, and fibroblast growth factor) are activated, perpetuating an inflammatory response. 29,30 In the investigation of pathogenic mechanisms involved in adenovirus infection, Mistchenko et al 31 found that high serum values for IL-6, IL-8, and tumor necrosis factor-␣ are associated with severity of adenovirus infection. We previously showed a significantly elevated percentage of neutrophils in BAL fluid from children with BO following adenovirus or Mycoplasma infection.…”
Section: Discussionmentioning
confidence: 99%
“…22,28 Vast arrays of cytokine and chemokine networks (those implicated include tumor necrosis factor-␣, IL-2, IL-8, RAN-TES [regulated upon activation, normal T-cell expressed and secreted], platelet-derived growth factor, transforming growth factor, and fibroblast growth factor) are activated, perpetuating an inflammatory response. 29,30 In the investigation of pathogenic mechanisms involved in adenovirus infection, Mistchenko et al 31 found that high serum values for IL-6, IL-8, and tumor necrosis factor-␣ are associated with severity of adenovirus infection. We previously showed a significantly elevated percentage of neutrophils in BAL fluid from children with BO following adenovirus or Mycoplasma infection.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, it could be shown that the expression of TGF-b 1 by alveolar macrophages and BALF cells from lung transplant recipients suffering from OB is enhanced [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-bs are able to act as negative and positive regulators of cell growth and induce differentiation, transformation, tissue repair, fibrosis and inflammatory responses [2±7]. Apart from this pathophysiological role of TGF-b in several fibrotic lung diseases [4±8], recent reports emphasize that alveolar macrophages and bronchoalveolar lavage fluid (BALF) cells obtained from patients with obliterative bronchiolitis (OB) after lung transplantation show an increased expression of TGF-b compared to patients free from OB [9,10]. OB is the most important complication in the long-term follow-up after lung and heart-lung transplantation, limiting life expectancy and quality of life [11].…”
mentioning
confidence: 99%
“…Studies in the inflammatory environment of BO have shown that TGF-b is one of the most important factors involved in the fibrotic process and high levels of TGF-b are found in the BAL from BO patients [148,[161][162][163][164][165]. Other pro-inflammatory cytokines, such as IL-8, TNF-a and IL-1b, are also highly expressed in BO patients [127,148,165].…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%